Investigating the influence of the progesterone receptor isoforms on androgen receptor activity in breast and prostate cancer cell lines - Rademeyer, Anina Zenda (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.